2010
DOI: 10.1161/circulationaha.110.955369
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 Suppresses Pathological Hypertrophy, Myocardial Fibrosis, and Cardiac Dysfunction

Abstract: Background-Angiotensin-converting enzyme 2 (ACE2) is a pleiotropic monocarboxypeptidase capable of metabolizing several peptide substrates. We hypothesized that ACE2 is a negative regulator of angiotensin II (Ang II)-mediated signaling and its adverse effects on the cardiovascular system. Methods and Results-Ang II infusion (1.5 mg ⅐ kg Ϫ1 ⅐ d Ϫ1) for 14 days resulted in worsening cardiac fibrosis and pathological hypertrophy in ACE2 knockout (Ace2 Ϫ/y ) mice compared with wild-type (WT) mice. Daily treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
471
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(495 citation statements)
references
References 42 publications
20
471
2
2
Order By: Relevance
“…Consistent with this, further in vivo studies using genetically engineered mice also found that ACE3 provides protective effects against chronic pressure overload‐induced cardiac hypertrophy, fibrosis, and dysfunction. Accumulating evidence has pointed out that ACE2 and its primary product Ang 1 to 7 play critical roles in the pathophysiology of cardiovascular disease, especially the protective actions against pathological cardiac hypertrophy 20, 21. We demonstrated that ACE3, as a new component of the ACE family, has the ability to impair Ang II‐ and pressure overload‐induced cardiac hypertrophy in this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with this, further in vivo studies using genetically engineered mice also found that ACE3 provides protective effects against chronic pressure overload‐induced cardiac hypertrophy, fibrosis, and dysfunction. Accumulating evidence has pointed out that ACE2 and its primary product Ang 1 to 7 play critical roles in the pathophysiology of cardiovascular disease, especially the protective actions against pathological cardiac hypertrophy 20, 21. We demonstrated that ACE3, as a new component of the ACE family, has the ability to impair Ang II‐ and pressure overload‐induced cardiac hypertrophy in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Our present findings are also consistent with the ability of the increased activation of MEK‐ERK1/2 signaling to exacerbate the pathological cardiac hypertrophy observed in other studies. Previous studies have demonstrated that the antagonistic roles of ACE2 on the worsening cardiac fibrosis and pathological hypertrophy were associated with the inhibition of the ERK1/2 signaling activity, which was markedly increased in ACE2‐deficient mice in response to pressure overload 20. Carabin, a protein expressed mainly in the immune system and the heart, was shown as a negative regulator of cardiac hypertrophy that induced by pressure overload and adrenergic stimulation, partly though inhibition of the MEK‐ERK1/2 signaling 24.…”
Section: Discussionmentioning
confidence: 99%
“…S1D). Two weeks after injection with rAAV9‐CYP2J2, the mice were exposed to 14 days of continuous infusion of either a saline control or Ang II (1 mg kg −1  day −1 ) to induce chronic hypertension and cardiac hypertrophy (Zhong et al ., 2010). Heart size was evaluated at the end of the 14‐day treatment period.…”
Section: Resultsmentioning
confidence: 99%
“…6 Intriguingly, treatment of wild type mice with recombinant human ACE2 reverses Ang II-induced pathological hypertrophy and oxidative stress. 6 In addition, recombinant human ACE2 therapy also attenuates the deterioration in cardiac function and development of pathological hypertrophy in wild type mice subjected to pressure overload via aortic banding.…”
Section: Article See P 1322mentioning
confidence: 99%
“…6 Intriguingly, treatment of wild type mice with recombinant human ACE2 reverses Ang II-induced pathological hypertrophy and oxidative stress. 6 In addition, recombinant human ACE2 therapy also attenuates the deterioration in cardiac function and development of pathological hypertrophy in wild type mice subjected to pressure overload via aortic banding. 6 Aortic banding of ACE2KO mice exacerbates the progression of LV hypertrophy, LV dilatation, and systolic dysfunction, which is associated with increased NADPH oxidase activity and subsequent oxidative stress, and is amendable to reversal following Ang 1-7 supplementation.…”
Section: Article See P 1322mentioning
confidence: 99%